Critical dimensions for the effective design and use of simulation exercises for emergency management in higher education. (9th October 2017) - Cooper, Vanessa; Forino, Giuseppe; Kanjanabootra, Sittimont; von Meding, Jason
Abstract : Purpose: There is a need to provide more effective learning experiences for higher education (HE) students in transdisciplinary contexts such as disasters and emergency management. While much has been written on the value of simulation exercises (SEs) for emergency management practitioners, research has focussed less on their value for HE students. The purpose of this paper is to identify how a practitioner-oriented framework for the design and use of SEs in emergency management is relevant to the HE context and how this framework may need to be adapted to support effective learning by HE students. Design/methodology/approach: An interpretive approach based on a qualitative content analysis of 16 semi-structured interviews with emergency management practitioners and educators is used to enable an in-depth understanding of the social phenomena to be obtained. Findings: The paper highlights that a framework for the design and use of SEs for emergency management practitioners is potentially valuable in the HE context but should be applied in a nuanced way. Research limitations/implications: The paper is based on a small number of interviews and future studies could usefully analyse a wider set of perspectives (e.g. students), using a variety of alternative methods (e.g. surveys), to further test and/or enrich the framework. Practical implications: Insights from the paper can inform the design and use of SEs in the HE context with a view to supporting more effective learning that better prepares students to operate during disaster events when they enter the emergency management workforce. Originality/value: This is the first paper that has investigated the value of a practitioner-oriented framework for the design and use of disaster SEs in the HE context. In so doing, the paper has highlighted how the dimensions of the framework apply in the HE context and has revealed other issues that need to be addressed to support effective learning by HE students.